Transferability of genomes to the next generation: the fundamental criterion for the biological species - Hohenegger, Johann (Zootaxa, 2012)
Biological species as the basic units in biodiversity unify organisms that are similar in structure, development andecological demands. Since Darwin’s work on the origin of species, intensive efforts have been mounted to find a criterionfor biological species that is common to all organisms, prokaryotes as well as eukaryotes, making species natural units.This has led to numerous species concepts, but none have met the requirement of universal application. Additionally, manyconcepts are based on criteria that can be used only for recognizing species (operational criteria), not defining the ‘being’or make-up of the species (explanatory criteria). The definition of a species concept proposed herein regards species as apool of similar genotypes interconnected in successive generations. This pool can be homogeneous or be divided into sub-pools. Interconnectivity within such pools is given by transferability, which means the potential to transfer completegenomes or genome halves to the next generation, perpetuating transferability. A change in genotype frequencies oversuccessive generations is caused by preferred or restricted genome transfer due to intrinsic and/or extrinsic factors.Speciation is defined as splitting up or splitting off a pool of genotypes into pools with differing genotype frequencies, in combination with a definite loss of transferability of genomes or genome halves between these pools.